Guarianthe, a generic name for the “Cattleya” skinneri complex - Dressler, Robert L. (Universidad de Costa Rica, 2016)
Molecular systematics, the comparison of DNA sequences, has brought a continuing revolution to plant taxonomy. In most cases, the results are intu- itively reasonable, even when they demand changing long-known names.